Induced Ovulation and Spawning in African Catfish (Clarias gariepinus) Using Different Doses of Ovaprim - Fouzi A. Mohamed; Ramzy A. Yousif; Ahmed A. Mohamed; Babeker I. Osman; Tajaldeen M. Abdalmwla (Jurnal Pijar MIPA, 2026)
The African catfish (Clarias gariepinus) is a cornerstone of tropical aquaculture, yet its reliance on induced spawning requires optimized hormonal protocols and broodstock management. This study investigated the effects of varying Ovaprim dosages and female-to-male broodstock ratios on the spawning success of C. gariepinus at the Fish Hatchery Unit, Sudan University of Science and Technology. Three treatments were evaluated: Treatment 1 (2:3 male : female ratio, 3.3 ml/kg Ovaprim), Treatment 2 (1:3 male : female ratio, 5 ml/kg Ovaprim), and Treatment 3 (2:3 male : female ratio, 3.7 ml/kg Ovaprim). Broodstock were conditioned for one week and fed a 2.5% body weight diet twice daily. The hormone was administered via intramuscular injection, and reproductive parameters, including latency period, ovulation rate, fertilization rate, and hatchability, were recorded. Data were summarized using descriptive statistics and one-way analysis of variance (ANOVA) to determine differences among treatments. The results demonstrated that Treatment 2 yielded significantly superior results, achieving a 50% larval production rate and a 10% survival rate, whereas Treatments 1 and 3 failed to produce any hatched larvae despite successful fertilization. This suggests that a 1:3 male-to-female ratio combined with a higher dosage (5 ml/kg) may overcome environmental or physiological latency in the Sudanese context. These findings emphasize the necessity of balancing hormonal induction with appropriate sex ratios to ensure hatchery sustainability.